REALITY SHOW INSPEKTUR IGUN: MATA-MATA KEKUASAAN DAN NORMALISASI TUBUH MODERN - Faisal, Andi (Universitas Hasanuddin, 2015)
Nowadays, the television programs in the form of reality show begin to emerge in our national television. By visualizing everyday life of ordinary people as ―real‖ in camera, reality show gained attention of its spectator. One of the interesting reality shows in Indonesia is Inspektur Igun. Inspector Igun, conducting as a fashion police, get directly into ―the reality‖ of people, such in mall, in market, in store-house, and so on, and perform inspection to the fashion style of people. Due to some supervised and disciplinary practices, the inspector change the uncivilized individu into the modern and civilized one in clothing.Using the panopticon of Foucauldian approach, this article aims to deconstruct the practices of discourse which tends to form the individu, to become obedient to ruling discourse. Through fashion, reality show becomes a panoptic mechanism in supervising and controlling activity of clothing in society in order to bear the identity of modern individu, an identity which become both marker of modernity andreligiousity, which is constructed through fashion.Keywords: Reality Show, Fashion, Panopticon, Normalization, Identity